Methylphenidate Treatment and Home Behavior - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Behavioral, situational, and temporal effects of treatment of ADHD with methylphenidate are reported in a study of 91 children receiving MPH (titrated to 0.7 mg/kg twice a day) or placebo for 4 months at the Hospital for Sick Children, Toronto, Canada.